Effects of Nationwide Program for Prevention and Control of Diabetes Initiated by the Ministry of Health on Elderly Diabetic Patients' Knowledge, Attitude and practice in Isfahan - Roohangiz Alirezaei Shahraki; Ahmad Aliakbari Kamrani‏; Robab Sahaf; Yadollah Abolfathi Momtaz (University of Social Welfare & Rehabilitation Sciences, 2019)
Objectives Diabetes is a chronic disease that is increasing in the world. This disease is spreading due to the population increase, aging process, lifestyle changes, inactivity, and inappropriate nutrition. The Nationwide Program for Prevention and Control of Diabetes is already underway for controlling this disease and its adverse effects, including the associated disabilities and immature mortality rate, economic costs, and improving the sufferers' life quality. This study aimed to investigate the effects of this program in Iran. Methods & Materials This was a cross-sectional study with a Pre-test-Post-test design. In total, 100 elderly patients newly diagnosed with diabetes were selected through convenience sampling method from Isfahan City, Iran. The required data were obtained using questionnaires on demographic and health data, as well as patients' knowledge, attitude, and practice. The data were gathered before and three months after the patients' entrance into the program. Results Of the total 100 patients participating in the study, 41% were male and 59% female; 42% retirees, 53% housekeepers, and 5% employees, of whom, 5% were males. Majority of them (44%) aged 60-64 years, and only 3% aged 80-84 years (minority). A total 88% of them lived with others and 12% lived alone. Moreover, 47% were illiterate, 15% were educated above diploma, 11% held a primary school degree, 6% had a junior high school degree, and 21% had a high school diploma. In addition, 77% of the patients suffered from this disease for 0-10 years, and 9% for 20-29 years; 55% had hypertension, 44% were overweight, 28% were obese, 53% had abdominal obesity, 71% suffered from hyperlipidemia, 66% reported a history of diabetes in their immediate family members, 4% were current smokers, 16% reported a history of smoking cessation, 3% were current alcohol drinkers, and 3% used to drink alcohol in the past. The patients' knowledge (median score) increased from 7 before initiating the program (Pre-test) to 10 after the completion of the program (Post-test) (P<0.001, z=-7.61); their attitude (median score) improved from 8 at Pre-test to 10 at Post-test (P<0.001; z=-6.84). The Mean±SD Pre-test and Post-test scores of the patients' practice were 35.60±6.38 and 41.91±5.23, respectively (P<0.001; t=-11.95). Conclusion The obtained results indicated the importance of the studied program for the prevention and control of elderly patients' diabetes by improving their knowledge, attitude, and practice. It is recommended that this program be implemented in all health centers of the country.